Исследования городищ юхновской культуры - Каравайко, Д.В. (Археологічні дослідження в Україні, 2009)
The paper presents the results of the research of hill-forts Kyselivka II and Buzhanka I of Yukhnivka culture on the territory of Novhorod-Siverskyi Polissya region. The materials obtained allowed the author not only to widen the source base, but also to get closer to the solving of the problem of burial customs and dating of Yukhnivka culture.